Opening the black box: Adoption of innovations in voluntary organisations - Yanuar Nugroho (The University of Manchester, Manchester Business School, 2009)
Despite the considerable attention paid to research into the adoption of technological innovations in government agencies and business firms, little attention has been paid to other types of organisations such as voluntary organisations (VOs). As a result, many things remain unknown: the patterns of uptake and adoption in VOs, the process of the transformation both of the organisations and the way they implement the innovation, and its implication. This paper attempts to address these problems. By presenting the case of Indonesian VOs at a theoretical level, this research is concerned with the diffusion of innovation and the effects on the practice of VOs and voluntary movements. These concerns are explored by examining two related empirical issues: (i) the links between innovation and organisational performance, and (ii) the construction of innovation diffusion and impacts in organisations that define those links.
Keywords: 330; adoption; technological innovations; voluntary organisations; not-for-profit; non-governmental